2009
DOI: 10.1519/jsc.0b013e31818eb0c5
|View full text |Cite
|
Sign up to set email alerts
|

Does Core Strength Training Influence Running Kinetics, Lower-Extremity Stability, and 5000-m Performance in Runners?

Abstract: Although strong core muscles are believed to help athletic performance, few scientific studies have been conducted to identify the effectiveness of core strength training (CST) on improving athletic performance. The aim of this study was to determine the effects of 6 weeks of CST on ground reaction forces (GRFs), stability of the lower extremity, and overall running performance in recreational and competitive runners. After a screening process, 28 healthy adults (age, 36.9 +/- 9.4 years; height, 168.4 +/- 9.6 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
136
0
8

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 162 publications
(155 citation statements)
references
References 11 publications
5
136
0
8
Order By: Relevance
“…Secondly, with skilled jumpers, a moderately unstable surface may not change the jumping strategy and thus not affect performance (Ferris & Farley, 1997). When examining the effects of core stability training in experienced runners, Sato and Mokha (2009) could not establish a significant link between core training over six weeks and any improvement in lower limb stability or ground reaction forces. They suggested that the mechanics of running…”
Section: Effects Of Surface Instability On Muscle Activity and Performentioning
confidence: 94%
See 1 more Smart Citation
“…Secondly, with skilled jumpers, a moderately unstable surface may not change the jumping strategy and thus not affect performance (Ferris & Farley, 1997). When examining the effects of core stability training in experienced runners, Sato and Mokha (2009) could not establish a significant link between core training over six weeks and any improvement in lower limb stability or ground reaction forces. They suggested that the mechanics of running…”
Section: Effects Of Surface Instability On Muscle Activity and Performentioning
confidence: 94%
“…For instance, when examining the effects of core stability training in experienced runners, Sato and Mokha (2009) could not establish a significant link between core training over six weeks and any improvement in lower limb stability or ground reaction forces. They suggested that the mechanics of running were not affected with experienced runners when core musculature conditioning is improved.…”
Section: Dysfunction Of Corementioning
confidence: 99%
“…The apparently crucial role of the CM during exercise has led to the suggestion that enhancing CM function would improve sports performance. However, most previous studies have failed to support this suggestion (10,18,19,22). Given the closely integrated relationship between CM and IM contributions to sports performance, it is perhaps unsurprising that interventions focussing only on the CM should fail to identify an improvement in sports performance.…”
Section: Introductionmentioning
confidence: 99%
“…Butcher et al 6 reported that LSEs significantly increased vertical takeoff velocity in athletes. Sato et al 32 also demonstrated the effectiveness of LSEs for improving performance.…”
mentioning
confidence: 98%